Integrated active lithium niobate photonic devices. (1st April 2023) - Wang, Min; Fang, Zhiwei; Lin, Jintian; Wu, Rongbo; Chen, Jinming; Liu, Zhaoxiang; Zhang, Haisu; Qiao, Lingling; Cheng, Ya
Abstract: We report on the fabrication of integrated active lithium niobate (LN) photonic devices such as waveguide amplifiers and tunable lasers using the photolithography-assisted chemo-mechanical etching (PLACE) technique. Specifically, a maximum internal net gain exceeding 20 dB is achieved in the LN waveguide amplifier, and an electro-optically tunable single-frequency laser with an ultra-narrow linewidth of 454.7 Hz is demonstrated in a high-Q LN microdisk. An electrically driven microring laser is demonstrated by the monolithic integration of a diode laser with an LN microring resonator. We also realize a hybrid integration of passive and active LN microdevices using a continuous lithographic processing approach. The integrated active LN photonic devices have a broad range of applications in light-wave communication, precision sensing and quantum information science.